An Argo‐Derived Background Diffusivity Parameterization for Improved Ocean Simulations in the Tropical Pacific. Issue 3 (10th February 2018) - Zhu, Yuchao; Zhang, Rong‐Hua
Abstract: Model biases are substantial in ocean and coupled ocean‐atmosphere simulations in the tropical Pacific Ocean, including a too cold tongue and too diffuse thermocline. These biases can be partly attributed to vertical mixing parameterizations in which the background diffusivity depiction has great uncertainties. Here based on the fine‐scale parameterization, the Argo data are used to derive the spatially varying background diffusivity, with a magnitude of O (10 −6  m 2  s −1 ) in the most area of tropical Pacific. This new scheme is then employed into the version 5.1 of the Modular Ocean Model‐based ocean‐only and coupled models, resulting in substantial improvements in ocean simulations, including a more realistic cold tongue and equatorial thermocline. The improved simulations can be attributed to the reduced cooling effects induced by weakened equatorial upwelling. Additionally, the subsurface cooling effect is attributed to the reduced heat transfer from the upper layer to the subsurface layer and the convergence of the colder water from off the equator. Key Points: Overestimated diapycnal mixing in OGCMs is partly responsible for model biases in the tropical Pacific Cold tongue and equatorial thermocline biases are reduced by ~25% by employing the Argo‐derived, spatially varying background diffusivity The improved simulations can be attributed to the regulation of the currents system, including an intensified subtropical cell and a weakened equatorial upwelling